Determinants of Trachomatous Inflammation-Follicular Among Children Aged 1 to 9 Years Old in a Rural Area of Gozamn District, Northwestern Ethiopia: A Matched Case-Control Study - Balew Adane; Asmamaw Malede; Birhanu Sewunet; Lake Kumlachew; Mekonnen Moges; Lebasie Woretaw; Tegegn Temesgen; Yenewa Bewket; Menberu Gete; Getasew Yirdaw; Agernesh Ayele; Metadel Adane (SAGE Publishing, 2023)
Background: Approximately 1.9 million people worldwide are blind or visually impaired due to trachoma, and trachoma remains endemic in 44 countries. Amhara in Ethiopia has the highest burden of trachoma in the world. A key indicator of whether active trachoma requires public health intervention is the incidence of trachomatous inflammation-follicular in children aged 1 to 9 years. However, limited study has been conducted on the determinants in rural communities. This study therefore aimed to fill this gap by identifying determinants in the Gozamn district of northwestern Ethiopia. Methods: A community-based case-control study was carried out between March 15 and April 30, 2021. Five or more follicles on the epitaxial conjunctivae that are larger than 0.5 mm were considered a case. Controls were free of any sign of trachoma. A semi-structured questionnaire and an observational checklist were used to gather the data, and STATA version 14 was used for the analysis. Using a 95% confidence interval, both bivariable and multivariable conditional logistic regression was performed. Results: A total of 726 mothers/caregivers participated in this study, with a participation rate of 98.4%. Children from poor families (mAOR = 4.68; CI: 2.80-6.21), households where the water source is far from home (>30 minutes) (mAOR = 4.91; KI: 1.37-12.56), mean daily water consumption (<20 l/c/d) (mAOR = 4.42; CI:1.71-11.39), face washing frequency less than once a day (mAOR = 10.64; CI: 2.58-18.84), cloth washing frequency once a month or less (mAOR = 9.18; CI: 2.20-18.62), and mothers or caregivers with poor knowledge of active trachoma (mAOR = 3.88; CI: 1.47-10.22) were determinants of trachomatous inflammation-follicular. Conclusions: We conclude that infrequent faces and clothes washing; unavailability of water, children in poor families, and poor knowledge of mothers/caregivers were risk factors. Health education initiatives about active trachoma, its prevention, and control methods focusing on personal hygiene are so required.